DEFINING THE ROOT CAUSE OF JAKARTA MBA STUDENTSâ€™ COMPLAINT USING 5-C TQM MODEL OF ACADEMIC EXCELLENCE - Salam, Karta Negara; Salam, Sri Wijaya (Faculty of Economics and Business, Hasanuddin University, 2019)
In the competitive world of education, there are many universities competing to improve the quality of education services, employee performance, and produce graduates with integrity and professional skills. One of them is SBM ITB Jakarta which is the location for the research. The purpose of this study was to determine the root causes of the quality of MBA ITB Jakarta services by using a qualitative approach and â€œ5C TQM of academic excellenceâ€ model as a guideline to improve the quality of education services. While for the technique of collecting data and analyzing qualitative data using interviews with respondents, the respondents in the study were university staff, lecturers, SBM ITB Jakarta management, and students. The results of the study concluded that there absence of such clear role from every unit involved (in this case SBM ITB Jakarta staff, lecturers, and management) as the root cause of student complaints related to the service quality of SBM ITB Jakarta. Miscommunication and misperception cannot be avoided because every unit has different perceptions and expectations toward each other.